The application of salvage surgery improves the quality of life and overall survival of extensively recurrent head and neck cancer after multiple operation plus radiotherapy - Zhang, Lirui; Xu, Qiaoshi; Liu, Huan; Li, Bo; Wang, Hao; Liu, Chang; Li, Jinzhong; Yang, Bin; Qin, Lizheng; Han, Zhengxue; Feng, Zhien (Frontiers in Oncology, 2022)
Objectives: The prognosis, choice of reconstruction and the quality of life (QOL) after salvage surgery (SS) for extensively locoregional recurrent/metastatic head and neck cancer (R/M HNC) is an important issue, but there are few reports at present. Materials and Methods: We analyzed extensively locoregional R/M HNC patients from March 1, 2015, to December 31, 2021 who underwent SS with latissimus dorsi or pectoralis major musculocutaneous flaps. QOL were accessed using QLQ-H&N35 and UW-QOL questionnaire. Wilcoxon signed-rank test was used to compare difference between pre- and post-QOL and Kaplan-Meier curves were used in estimate overall survival (OS) and disease-free survival (DFS). The literature review summarized recent 10 years clinical trials of nonoperative treatment in R/M head and neck cancer. Results: 1362 patients were identified and 25 patients were analyzed after screened. Median age at surgery was 59 years (range 43-77), 15/25(60%) were male and 22/25(88%) chose latissimus dorsi flap. Better mean pain score after applying massive soft tissue flaps revealed relief of severe pain(p<0.001) which strongly associated with improvement of QOL. The improved mean overall QOL score after surgery revealed a better QOL(p<0.001). As of June 1, 2022, 11/25 (44%) of the patients were alive. The 1-year, 2-year OS after SS was 58.4% and 37.2%, while the 1-year, 2-year DFS was 26.2% and 20.9%. The median OS of our study was better than nonoperative treatment of 11 included clinical trials. Conclusions: R/M HNC patients underwent SS can obtain survival benefit. The application of massive soft tissue flap in SS could significantly enhance the QOL for patients with extensively locoregional R/M HNC, especially by relieving severe pain.